In Vivo Biodistribution, Clearance, and Biocompatibility of Multiple Carbon Dots Containing Nanoparticles for Biomedical Application - Jinfeng Liao (MDPI AG, 2021)
Current research on the use of carbon dots for various biological systems mainly focuses on the single carbon dots, while particles that contain multiple carbon dots have scarcely been investigated. Here, we assessed multiple carbon dots-crosslinked polyethyleneimine nanoparticles (CDs@PEI) for their in vivo biodistribution, clearance, biocompatibility, and cellular uptake. The in vivo studies demonstrate three unique features of the CDs@PEI nanoparticles: (1) the nanoparticles possess tumor-targeting ability with steady and prolonged retention time in the tumor region. (2) The nanoparticles show hepatobiliary excretion and are clear from the intestine in feces. (3) The nanoparticles have much better biocompatibility than the polyethyleneimine passivated single carbon dots (PEI-CD). We also found that pegylated CDs@PEI nanoparticles can be effectively taken up by the cells, which the confocal laser scanning microscope can image under different excitation wavelengths (at 405, 488, and 800 nm). These prior studies provide invaluable information and new opportunities for this new type of intrinsic photoluminescence nanoparticles in carbon dot-based biomedical applications.